Science in society : an introduction to social studies of science - Bucchi, Massimiano, 1970- (Routledge, 2004)
Without assuming any scientific background, Bucchi provides clear summaries of all the major theoretical positions within the sociology of science, using many fascinating examples to illustrate them.